The Green Shape, the Rose Shape, the Green Shape, the Rose Shape - Woschek, Philipp; Landwehrjohann, Max (Satura, 2022)
Ms. Faßbender was indignant. A grease stain adorned her glasses, her slouch hat losing the battle against the heat, her neck protector stuck to her like a wet shower curtain. And now she was standing before this impossible shrub: a dog rose that had the impudence to blossom and carry fruit at the same time, even though the blooming period was over, and the fruit shouldn’t ripen for two months at the earliest. This could not be.